2009
DOI: 10.1089/apc.2008.0194
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Social Support: Global and Specific Social Support Experiences of HIV-Infected Youth

Abstract: This study examined the nature, type, and source of social support available to a diverse group of HIV-infected adolescents and the relationship between social support and depression. Data were obtained from the baseline assessment of Adolescent Impact, a behavioral intervention conducted in 2003-2006 involving 166 HIV-infected youth, ages 13-21, in care at four urban medical centers. Youth completed the Medical Outcomes Study Social Support Survey, Beck Depression Inventory, and questions about HIV-specific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 34 publications
6
38
4
1
Order By: Relevance
“…More specifically, we found that the association between SWL and PTG was stronger in the group of single participants than in the group of participants in stable relationships. Several authors noted that for PLWH, being in a stable relationship is an important source of life satisfaction, which is additionally positively related to affective well-being (Abramowitz et al 2009;Mavandadi et al 2009). Therefore, perhaps the role of SWL for PTG may be not as important as for single participants, but more research is needed to verify this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, we found that the association between SWL and PTG was stronger in the group of single participants than in the group of participants in stable relationships. Several authors noted that for PLWH, being in a stable relationship is an important source of life satisfaction, which is additionally positively related to affective well-being (Abramowitz et al 2009;Mavandadi et al 2009). Therefore, perhaps the role of SWL for PTG may be not as important as for single participants, but more research is needed to verify this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis and management of HIV/AIDS are associated with significant physical and psychosocial morbidity (Bogart et al, 2000). Previous studies have shown that individuals living with HIV/AIDS require support and health information in order to help manage the disease (Abramowitz et al, 2009) but that their needs have not always been met (Schrimshaw, Siegel, Schrimshaw, & Siegel, 2003;Serovich, Brucker, & Kimberly, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…2 The impact on teen girls is particularly notable. In 2004, teen girls in the United States represented 43% of AIDS cases among those aged [13][14][15][16][17][18][19], and young women aged 20-24 represented 33% of AIDS cases in their respective age group. 2 Women of color, particularly African American women, are disproportionately impacted by HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%